Evaluation of temperature regime of rods of inductor of MHD stirrer for possible use in industrial aluminium furnace - Lekomtsev, Sergey Vladivirovich; Khripchenko, Stanislav Yurievich (Computational Continuum Mechanics, 2017)
In the production of aluminum alloys the melt must be stirred in the bath of a furnace. Generally, stirring is provided by MHD-stirrers. However, MHD-stirrers commonly used in real production are the linear traveling field inductors which cannot be sufficiently effective by reason of their design features. Their sizes are much less than the linear dimensions of the bath and their poles are outside the bath walls and the insulation layer, which essentially reduces the influence of a magnetic field on the molten metal. The electrical power consumed by these stirrers is great (hundreds of kilovolt-ampere). An alternative to these stirrers may be a device with rods connected in parallel to a 3-phase power supply and placed in close proximity to the molten metal, immediately under the bath bottom. The main problem associated with this device is the cooling of rods (Joule heat dissipation released during the passage of electric current and heat from the molten metal bath in the furnace through them). The simplest way to carry out the released heat is the convective movement of air in the tubular rods (there is no need for special additional equipment). For multivariate engineering calculations at the stage of model designing it is necessary to determine the values of a convective air flow in the hollow rods of the inductor of a MHD-stirrer. In the present paper we propose a model for the convective air flow passing through the rods of the inductor of an MHD-stirrer. Based on this model and using the results of physical experiments performed in this study, we have derived a simple semi-empirical formula for approximate computation of the convective velocity of air in the hollow rods of an MHD-stirrer.
Keywords: aluminum reflecting furnace; rod MHD-stirrer; temperature field; heat transfer; heat flow; thermal conductivity; turbulent flow; semi-empirical model